Sustainable concrete solutions for green infrastructure development: A review - Md Nazeem Akhtar; Rizwan Khan; Abdur Rahman Siddiqui (Journal of Sustainable Construction Materials and Technologies)
This review paper explores the utilization of sustainable concrete materials in the developmentof green infrastructure. The primary objective is to investigate various concrete solutions thatenhance environmental performance while maintaining structural integrity. The study inte-grates concrete with green infrastructure elements such as permeable concrete, green roofs,vegetated systems, bioswales, and vegetated channels. These elements are essential for man-aging stormwater, reducing urban heat islands, and promoting biodiversity in urban areas.The paper also examines optimized concrete mixtures designed to improve durability andreduce carbon emissions by incorporating alternative materials like recycled aggregates andsupplementary cementitious materials. Additionally, innovative formwork and constructionpractices are analyzed to assess their contribution to minimizing resource consumption andwaste. By aligning concrete design with green infrastructure objectives, the study highlightsthe potential of these solutions to mitigate environmental impacts, including reduced energyconsumption and lower greenhouse gas emissions. The findings offer valuable insights intothe role of sustainable concrete in future urban planning, emphasizing its capacity to supportresilient, eco-friendly infrastructure while meeting the growing demands of urbanization. Theresearch ultimately contributes to the broader discourse on green construction practices, of-fering practical guidelines for engineers and urban planners.